Innovations in digital research methods - Halfpenny, Peter; Procter, Rob (London SAGE, 2015)
Vast amounts of digital data are now generated daily by people as they go about their lives, yet social researchers are struggling to exploit it. At the same time, the challenges faced by society in the 21st century are growing ever more complex, and demands research that is bigger in scale, more collaborative and multi-disciplinary than ever before. This cutting-edge volume provides an accessible introduction to innovative digital social research tools and methods that harness this 'data deluge' and successfully tackle key research challenges. Contributions from leading international researchers cover topics such as: Qualitative, quantitative and mixed methods research; Data management; Social media and social network analysis; Modeling and simulation; Survey methods; Visualizing social data; Ethics and e-research. The future of social research in the digital age. This vibrant introduction to innovative digital research methods is essential reading for anyone conducting social research today.
Chapter 1: Introduction and overview - Peter Halfpenny and Rob ProctorChapter -- 2: The Changing social data landscape - Kingsley Purdam and Mark ElliotChapter -- 3: Exploiting new sources of data - Kingsley Purdam and Mark Elliot -- Chapter 4: Survey methods: challenges and opportunities - Joe Murphy -- Chapter 5: Advances in data management for social survey - Paul S. Lambert -- Chapter 6: Modelling and simulation - Mark Birkin and Nick Malleson -- Chapter 7: Contemporary developments in statistical software for social scientists - Paul S. Lambert, William J. Browne and Danius T. Michaelides -- Chapter 8: Text mining and social Media: when Quantitative Meets Qualitative, and Software Meets People - Lawrence Ampofo, Simon Collister, Ben O'Loughlin and Andrew Chadwick -- Chapter 9: Digital Records and the Digital Replay System - Andy Crabtree, Paul Tennent, Pat Brundell and Dawn Knight -- Chapter 10: Social Network Analysis - Robert Ackland and Jonathan Zhu -- Chapter 11: Visualising spatial data and social media - Michael Batty, Steven Gray, Andrew Hudson-Smith, Richard Milton, Oliver O'Brien and Flora Roumpani -- Chapter 12: Ethical Praxis in e-research - R.J. Anderson and Marina JirotkaChapter 13: Sociology and the digital challenge - Mike Savage.
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Methodology; Internet research; Social media -- Research; Internet -- Social aspects